The Protocol to the African Charter on Human and Peoples' Rights on the Rights of Women in Africa: a commentary - Rudman, Annika; Musembi, Celestine Nyamu; Makunya, Trésor Muhindo (Pretoria University Law Press (PULP), 2023)
Since its adoption on 11 July 2003, the Protocol to the African Charter on Human and Peoples' Rights on the Rights of Women in Africa (the Maputo Protocol) has become a landmark on the African human rights landscape. It has steadily gained prominence as a trail-blazing instrument, responsive to the diverse realities of women on the African continent. This comprehensive Commentary on the Maputo Protocol, the first of its kind, provides systematic analysis of each article of the Protocol, delving into the drafting history, and elaborating on relevant key concepts and normative standards. This Commentary aims to be a 'one-stop-shop' for anyone interested in the Maputo Protocol, such as researchers, teachers, students, practitioners, policymakers and activists.